The art and craft of political theory - Thiele, Leslie Paul (New York, NY Routledge, an imprint of the Taylor & Francis Group, 2019)
"The Art and Craft of Political Theory provides a critical overview of the discipline's core concepts and concerns and its development of critical thinking and practical judgment. The field's interdisciplinary strengths are deployed to grapple with emerging issues and engage afresh enduring ideals and quandaries. While conventional definitions of key concepts are provided, original and controversial perspectives are also explored, revealing continuity in a tradition of thought while emphasizing its diversity and innovations. The Art and Craft of Political Theory illustrates the analytic and interpretive skills, the moral and philosophic discernment, and the historical knowledge needed to appreciate a tradition of thought, to contest its claims, and to make good use of its insights. Topics include: - Science, Ideology, and Normative Theory - Biology, Culture, Human Nature, Power and Violence - Ancient, Modern, and Postmodern Political Thought - Liberty, Equality, Justice, Reason, and Democracy - Racial, Religious, Gender, and Economic Identities - Liberalism, Socialism, Capitalism, Communism, Anarchism, Feminism, and Environmentalism - Social Media, Automation, Artificial intelligence and other Emerging Technologies This concise, lively, and accessibly written book is essential reading for all students of political theory"--Provided by publisher.
Theory, ideology and irony -- Human nature, power and politics -- Ancient, modern and postmodern political thought -- The politics of identity and difference -- Enduring challenges in a changing world -- Technology and the human prospect.
Includes bibliographical references and index.
Keywords: Political science -- Philosophy